High-Fat Diet Augments VPAC1 Receptor-Mediated PACAP Action on the Liver, Inducing LAR Expression and Insulin Resistance - Masanori Nakata; Boyang Zhang; Yifei Yang; Takashi Okada; Norihito Shintani; Hitoshi Hashimoto; Toshihiko Yada (Journal of Diabetes Research)
Pituitary adenylate cyclase-activating polypeptide (PACAP) acts on multiple processes of glucose and energy metabolism. PACAP potentiates insulin action in adipocytes and insulin release from pancreatic β-cells, thereby enhancing glucose tolerance. Contrary to these effects at organ levels, PACAP null mice exhibit hypersensitivity to insulin. However, this apparent discrepancy remains to be solved. We aimed to clarify the mechanism underlying the antidiabetic phenotype of PACAP null mice. Feeding with high-fat diet (HFD) impaired insulin sensitivity and glucose tolerance in wild type mice, whereas these changes were prevented in PACAP null mice. HFD also impaired insulin-induced Akt phosphorylation in the liver in wild type mice, but not in PACAP null mice. Using GeneFishing method, HFD increased the leukocyte common antigen-related (LAR) protein tyrosine phosphatase in the liver in wild type mice. Silencing of LAR restored the insulin signaling in the liver of HFD mice. Moreover, the increased LAR expression by HFD was prevented in PACAP null mice. HFD increased the expression of VPAC1 receptor (VPAC1-R), one of three PACAP receptors, in the liver of wild type mice. These data indicate that PACAP-VPAC1-R signaling induces LAR expression and insulin resistance in the liver of HFD mice. Antagonism of VPAC1-R may prevent progression of HFD-induced insulin resistance in the liver, providing a novel antidiabetic strategy.